AN ANALYSIS ON STUDENTS’ PROBLEM IN WRITING A NARRATIVE TEXT AT ELEVENTH GRADE OF SMAN 1 KOTO KAMPAR HULU - Yunanda, Nurma; Asilestari, Putri; Hardi, Vitri Anggraini (TELL - US JOURNAL, 2023)
This study aims to describe the problems in writing narrative text for class XI students of SMAN 1 Koto Kampar Hulu, describing the problems faced by students in write narrative texts, and provide solutions or ways to overcome problems faced by students. This study uses a qualitative description method. Technique data collection was obtained by using interview techniques and documentation, and the data obtained were analyzed using Triangulation data sources and method triangulation. The results showed that in writing narrative text, in class XI students of SMAN 1 Koto Kampar Hulu carried out based on 2013 curriculum, class XI English learning syllabus, and carried out according to the English lesson plan for narrative text teaching materials. The problems faced in writing narrative texts are: teacher teaching to students is not optimal, students' motivation is low in writing narrative text, How to overcome these difficulties is that teachers are given training and guidance regarding learning and students are given attention, motivation to be active in learning